2004
DOI: 10.1103/physrevlett.92.117406
|View full text |Cite
|
Sign up to set email alerts
|

Low Energy Electronic Excitations in the Layered Cuprates Studied by CopperL3Resonant Inelastic X-Ray Scattering

Abstract: We have measured the resonant inelastic x-ray scattering (RIXS) spectra at the Cu L3 edge in a variety of cuprates. Exploiting a considerably improved energy resolution (0.8 eV) we recorded significant dependencies on the sample composition and orientation, on the scattering geometry, and on the incident photon polarization. The RIXS final states correspond to two families of electronic excitations, having local (dd excitations) and nonlocal (charge-transfer) character. The dd energy splitting can be estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
118
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(124 citation statements)
references
References 23 publications
6
118
0
Order By: Relevance
“…Our analysis has shown that the contribution of Y (2) The present theory is applicable to analyze the magnetic excitation spectrum at the Cu M 2,3 -edge. In the following, we focus on the M 3 -edge case.…”
Section: B M3-edge Spectrummentioning
confidence: 95%
See 1 more Smart Citation
“…Our analysis has shown that the contribution of Y (2) The present theory is applicable to analyze the magnetic excitation spectrum at the Cu M 2,3 -edge. In the following, we focus on the M 3 -edge case.…”
Section: B M3-edge Spectrummentioning
confidence: 95%
“…Recently, progress in the experimental technique of RIXS enables us to carry out higher energy resolution measurement, 2,3 for instance, in several transition metal oxides like the cuprates. [4][5][6][7] Hill et al have succeeded in detecting the magnetic excitation spectra peaked around 500 meV energy region at the Cu K-edge in La 2 CuO 4 .…”
Section: Introductionmentioning
confidence: 99%
“…We note that the scattered intensities shown here are not energy resolved, and have some contribution from inelastic scattering as well. However, the inelastic scattering comes mainly from inter-orbital transitions (dd excitations), with small contributions from paramagnon and charge transfer excitations [15,[26][27][28]. The inelastic contribution is only weakly dependent on q and can be subtracted as a flat background.…”
Section: Methodsmentioning
confidence: 99%
“…From a consideration of the excitation energy of this feature, a possible origin is the local dd-excitation which has been observed around 1.5 eV. 24,25 However more detailed measurements are necessary to draw definitive conclusions.…”
Section: Low-energy Excitationmentioning
confidence: 99%